The Concept of Religion of the Future according to the Esoteric Community of Wisła in the Interwar Period - Trzcińska, Izabela (Studia religiologica, 2020)
The purpose of the article is to present the idea of a religion of the future as conceived by the esoteric community of Wisła in Cieszyn Silesia during the interwar period. Esoteric interpretations of Christianity formed its basis, inspired mainly by the Polish romantic tradition connected with Bible reading, as well as the esoteric and spiritual ideas that were popular at that time, originating from Theosophy and spiritism. An important role in this context was played by considerations on the salvational mission of Christ, albeit presented in a perennialist and Gnostic manner. The esoteric spirituality from Wisła of the interwar period later paved the way for a modern alternative spirituality in Poland.